Socio-Political Turbulence of the Ottoman Empire: Reconsidering Sufi and Kadizadeli Hostility in 17th Century - Ahya Ulumiddin (Ulumuna, 2016)
The fierce hostility that happened between the Kadizadelis and the Sufis during the 17th century of the Ottoman Empire is not the new issue in Islamic civilization discourses. During this period, the empire suffered from massive decadences in almost all sectors. Kadizadelis believed that such phenomenon did not come out of the void. They insisted that the crux of the problem was primarily laid in the heresies and religious innovations (bidᶜah) that were promoted largely by the Sufis. Embarking from this suspicion and anxiety, they initiated propagandas in which they aimed to bring back people to re-embracement of the primordial teachings of Islam. Nevertheless, many historians and scholars have doubted Kadizadelis attempts. They suspected that there were other non-religious motives that stirred their revival agendas. This paper presents an analysis that aims to challenge the commonly believed notion in which the Sufis and the Kadizadelis were totally adversarial. DOI: http://dx.doi.org/10.20414/ujis.v20i2.807